2015
DOI: 10.1080/08952841.2014.934645
|View full text |Cite
|
Sign up to set email alerts
|

Worry and Bother: Factors in Rural Women’s Health Decision Making

Abstract: This exploratory study examined older rural women's health decision making. Thirty-three rural women were recruited to participate in semistructured qualitative interviews. Major themes emerged that focused on rural women's comments regarding their concerns about not worrying or bothering their children with personal health matters. Themes were discussed in the context of an ethic of care. Results suggest that it is important for mental health professionals, family physicians, social workers, and other practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…25 Studies into rural culture have revealed distinctions relevant to health and embodiment, including the reliance on independence and religion, a focus on capacity to work and not burdening others, a fear of stigma and disclosure, and a distrust in health care. [26][27][28][29][30] Therefore, rurality may materially and socially shape individuals' health care experiences, behaviors, and social treatment.…”
Section: Weight Stigmamentioning
confidence: 99%
“…25 Studies into rural culture have revealed distinctions relevant to health and embodiment, including the reliance on independence and religion, a focus on capacity to work and not burdening others, a fear of stigma and disclosure, and a distrust in health care. [26][27][28][29][30] Therefore, rurality may materially and socially shape individuals' health care experiences, behaviors, and social treatment.…”
Section: Weight Stigmamentioning
confidence: 99%